2019
DOI: 10.1051/bioconf/20191202026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aflatoxins in rustically wines from eastern Romania using the direct real time method (DART)

Abstract: Romania has a long tradition regarding the production of wine rustically or household products. Each householder has the possibility for making its own wine from its own grape vines. Most of them are made and kept using almost no interventions or treatments no corrections or added substances, which could protect them from eventual diseases, which may appear during the winemaking process. The grapes are collected manually by each family alone and it can be called is itself a ritual specific to the each area and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Contaminated wine samples reached 87.5% of the analyzed ones, and the AFB2 levels ranged from 1.25 to 25.73 µg/L. Nistor et al [14] detected in Romanian wines the highest concentrations for AFB1 and AFG1 (between 26.68 and 33.68 µg/kg). Aflatoxins and aflatoxins-producing strains have also been detected in grapes and grape must in North African countries-Lebanon and Tunisia [15,16].…”
Section: Introductionmentioning
confidence: 92%
“…Contaminated wine samples reached 87.5% of the analyzed ones, and the AFB2 levels ranged from 1.25 to 25.73 µg/L. Nistor et al [14] detected in Romanian wines the highest concentrations for AFB1 and AFG1 (between 26.68 and 33.68 µg/kg). Aflatoxins and aflatoxins-producing strains have also been detected in grapes and grape must in North African countries-Lebanon and Tunisia [15,16].…”
Section: Introductionmentioning
confidence: 92%
“…In sweet wine from Italy, Di Stefano et al [63] found AFB1 ranging from 0.017-0.035 μg/L, and AFB2 from 0.013-0.016 μg/L. A screening in different wines in Romania measured AFB1 ranging from 12.12 to 33.68 μg/L [82]. However, there is no established limit for aflatoxins in wines, and studies on the content of aflatoxins in wines are limited.…”
Section: Aflatoxinsmentioning
confidence: 99%
“…To monitor OTA presence in wine, different research works have investigated its fate during winemaking [75][76][77] and included efforts to remove it from the final product [78,79]. Apart from OTA, the presence of several other mycotoxins in wine has been studied, with the majority concerning AFBs [80,81], but also other mycotoxins such as FBs [82,83], AOH and other Alternaria toxins [84,85], PAT, CIT, and other Penicillium toxins [39,86,87].…”
Section: Mycotoxins In the Grape Food Chainmentioning
confidence: 99%